PENGARUH MODEL PBL DENGAN PENDEKATAN DEEP LEARNING BERBANTUAN SMART BOX TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Windy Sintia; Anwar Ardani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Problem solving ability is an important ability that needs to be developed in elementary mathematics learning. However, teacher centered learning tends to provide limited opportunities for students to understand problems, determine appropriate strategies, carry out solutions, and evaluate the results. This study aimed to determine the effect of the PBL model with a Deep Learning approach assisted by Smart Box media on the problem solving ability of fourth grade elementary school students. This study employed a quantitative approach with a quasi experimental method using a Nonequivalent Control Group Design. The research subjects consisted of 58 fourth grade students from State Elementary School Ajibarang Wetan, comprising 30 students in the experimental class and 28 students in the control class. Data were collected using an essay test measuring students problem solving ability. Data analysis included normality and homogeneity tests, followed by hypothesis testing using an Independent Sample t-Test. The results showed that the mean posttest score of the experimental class was 76.50, while the control class obtained a mean score of 62.89. The hypothesis test resulted in a of 3.2385 and a of 2.003, indicating that the was greater than the . Thus, is rejected and is accepted, indicating a difference in problem solving ability between students who participated in instruction using the PBL model with a Deep Learning approach assisted by Smart Box media and students who underwent conventional instruction.